2016
DOI: 10.1016/j.ajo.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Retinal Microvascular Changes in Uveitis Using Spectral-Domain Optical Coherence Tomography Angiography

Abstract: Purpose To quantify retinal capillary density and morphology in uveitis using SD-OCTA. Design Cross-sectional, observational study Methods Healthy and uveitic subjects were recruited from two tertiary care eye centers. Prototype SD-OCTA devices (Cirrus, Carl Zeiss Meditec, Inc., Dublin, CA) were used to generate 3×3 mm2 OCTA images centered on the fovea. Subjects were placed into 3 groups based on the type of optical microangiography (OMAG) algorithm used for image processing (intensity-and/or phase) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 26 publications
3
137
0
Order By: Relevance
“…Fractal dimension has previously been used to investigate the retinal microvasculature in fundus [49][50][51][52] or OCTA 10,12,13 images. By evaluating pattern repetition at different scales, 53 fractal dimension is particularly adapted to assess the integrity of arborized vascular networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractal dimension has previously been used to investigate the retinal microvasculature in fundus [49][50][51][52] or OCTA 10,12,13 images. By evaluating pattern repetition at different scales, 53 fractal dimension is particularly adapted to assess the integrity of arborized vascular networks.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal dimension is a promising endpoint to measure vascular network disorganization in OCTA images, which has been used successfully in diabetic retinopathy [10][11][12] and posterior uveitis. 13 Ocular irradiation by I-125 plaque brachytherapy induces microvascular changes detected by OCTA. 14,15 However, the consequences of proton-beam therapy, a major treatment modality for uveal melanoma, have not been assessed by OCTA.…”
mentioning
confidence: 99%
“…[1315] These parameters are designed to quantitatively characterize capillary density (VD, SD) and capillary morphology (FD, VDI) since both density (“dropout”) and morphology (e.g. vessel dilation) are known variables in the development and progression of retinal vascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have reported enlarged foveal avascular zone (FAZ) area in retinal ischaemic diseases such as diabetic retinopathy (DR)10 and retinal vascular obstruction (RVO)11; decreased FAZ area in retinopathy of prematurity12; decreased vessel density in DR10 and glaucoma13; lower fractal dimension in RVO,11 DR10 and uveitis eyes14; increased vessel diameter index (VDI) in RVO11 and DR10; and decreased FAZ circularity in glaucoma15 and DR 10. These studies demonstrate that quantitative OCTA metrics may provide useful information for the diagnosis of ocular diseases potentially.…”
Section: Introductionmentioning
confidence: 99%